THE USE OF DIGITAL CHOICE BOARD TO ENGAGE JUNIOR HIGH SCHOOL STUDENTS IN LEARNING NARRATIVE TEXT - Erfira Maya Shinta (Universitas Muhammadiyah Prof. DR. HAMKA, 2021)
Students are having diverse learning styles, personalities, needs, interests, and intelligences, which affect students’ engagement to the teaching and learning processes including English Language Teaching and Learning. And therefore teacher should accommodate those diversities by differentiating the instructions that provide varieties of activities students can choose based on their own interests. Using Digital Choice Board under the framework of differentiated instructions philosophy, teacher’s effort to engage the students by giving them “Merdeka Belajar” and freedom to choose can be implemented. This paper discuss the implementation of Digital Choice Board to engage students in EFL teaching and learning and provide evidence how Digital Choice Board can improve students’ engagement in learning narrative text.